Development of a Concept Dictionary to Standardize Definitions and Classifications While Working With a Common Repository of Linked Administrative Data. (2018) - Macdonald, Erin; Chu, Anna; Cooper, Michelle; Croxford, Ruth; Duchen, Raquel; Fung, Kinwah; Gandhi, Sima; Gatley, Jodi; Jin, Fiona; Khuu, Wayne; Kopp, Alex; Maclagan, Laura; et al.
No abstract available